2013
DOI: 10.1590/0037-8682-1451-2013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic detection of metallo-β-lactamases in Pseudomonas aeruginosa and Acinetobacter baumannii isolated from hospitalized patients in São Luis, State of Maranhão, Brazil

Abstract: Introduction: Acquired metallo-β-lactamases (MβL) are emerging determinants of resistance in Pseudomonas aeruginosa and Acinetobacter baumannii. The objectives of this study were to phenotypically detect MβL in imipenem-resistant P. aeruginosa and A. baumannii, to investigate the association between MβL-positive strains and hospitals, and to compare the resistance profi les of MβL-producing and non-MβL-producing strains. Methods: The approximation disk and combined disk assay methods were used in this study. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
1
0
4
Order By: Relevance
“…Noori et al (2014) found the highest percentage of MBL producing A. baumannii in respiratory tract specimens (52.8%) followed by urine (26.9%) and blood (7.4%) [ 7 ]. Another study was conducted by de Carvalho et al (2013) which described that the most frequent site of isolation was tracheal secretion (56.3%), followed by the catheter tip (16.9%), blood (7%), and urine (7%) [ 24 ]. The sites of infection can vary in various patients and this could be associated with the type of interventional procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Noori et al (2014) found the highest percentage of MBL producing A. baumannii in respiratory tract specimens (52.8%) followed by urine (26.9%) and blood (7.4%) [ 7 ]. Another study was conducted by de Carvalho et al (2013) which described that the most frequent site of isolation was tracheal secretion (56.3%), followed by the catheter tip (16.9%), blood (7%), and urine (7%) [ 24 ]. The sites of infection can vary in various patients and this could be associated with the type of interventional procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A Pseudomonas aeruginosa é uma bactéria oportunista, considerada um dos principais agentes de infecção nosocomial em hospitais associada múltipla resistência a antibacterianos (CARVALHO et al, 2013;SILVA JÚNIOR et al, 2014;ROCHA et al, 2019), sendo apontada como um problema de saúde pública (NUNES et al, 2023). Em animais, principalmente cães, este microrganismo está associado a otite sendo relatados ocorrência de P. aeruginosa multirresistentes (MDR) a antibióticos envolvidos (ARIAS et al, 2017).…”
Section: Introductionunclassified
“…, Goiânia, v. 47, p. [1][2][3][4][5][6][7][8][9][10][11]2020 Introdução A resistência aos antimicrobianos é um problema de saúde pública emergente, infecções que eram tratadas com relativa facilidade podem voltar a matar cerca de 10 milhões de pessoas até 2050 1 . As bactérias que possuem resistência a três ou mais classes de antimicrobianos são denominadas multirresistentes (MDRs) 2 .…”
unclassified
“…No Rio Grande do Sul, de 70 isolados analisados (95,7%) foram cepas ERC. Em São Luís -MA, (36,4%) das cepas de P. aeruginosa provenientes de três hospitais foram resistentes ao imipenem [4][5] . Já em Goiânia a taxa de resistência detectada foi de (76,8%) para carbapenêmicos em isolados de A. baumannii, essa resistência também foi detectada em Belém [6][7] .…”
unclassified
See 1 more Smart Citation